Assessment of young children : a collaborative approach - Fiore, Lisa B., 1970- (New York, NY : Routledge, 2021)
"In an era where assessment mandates tend to minimize or dismiss individual differences and creativity, resulting in punitive outcomes or inertia, this essential guide provides teachers with a collaborative approach to assessment that emphasizes the importance of bringing children and families into the process. Now in its second edition, Assessment of Young Children explores both standardized and authentic assessment, work sampling systems, and observation skills. Fully updated with current standards and research, this new edition also features an enhanced focus on trauma-informed practices, culturally and linguistically diverse learners, and family involvement. Lively and engaging, chapters help readers cultivate developmentally appropriate practice, create appropriate expectations, examine and celebrate children's work, interact in groups, and improve their reflective teaching. Accounts of real experiences from children, families, teachers, and administrators provide on-the-ground models of assessment strategies and demonstrate how children are affected. Exploring a variety of ways to observe and assess young children in their natural environments, this critical volume encourages an assessment strategy where the child remains the focus and collaboration with children, families, and colleagues creates an image-not a diagnosis-of the child that is empowering rather than constraining"--
OCLC-licensed vendor bibliographic record.
Keywords: Early childhood education -- Evaluation; EDUCATION / Preschool & Kindergarten